PENGUATAN LITERASI MATEMATIS MELALUI MATRIKULASI TERINTEGRASI LINGKUNGAN PADA ANAK LINGKUNGAN TAMO DHUA - Arifin, Sartika; Aprisal, Aprisal; Muliadi, Aldi; Adinang, Adinang; Wahyuni, Wahyuni; Sipaami, Sipaami; Auliah, Iqrimah Nur; Maharani, Yunita; Fahrezi, Ahmad (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Mathematic literacy is important in children from an early age because mathematics plays a very important role in everyday life. Introducing mathematical concepts early, building strong numeracy skills and involving students in meaningful mathematical activities. The purpose of this service is to reinforce mathematical literacy through integrated matriculation of the environment for children in the Tamo Dhua environment. Matriculation activities were carried out for 5 days for children in the Tamo Dhua Environment consisting of grades I to VII to strengthen children's mathematical literacy by teaching mathematical concepts and linking them to examples of everyday life. The results of this service activity are that children's mathematical literacy has increased, children increasingly like mathematics and children are very enthusiastic about participating in the matriculation activities.